Estimated efficiency of domain agents sites in mobile networks of large dimension - Жуков, И. А.; Давиденко, И. Н. (Problems of Informatization and Control, 2007)
The way of increase of routing process efficiency on the basis of agents system is offered. The analysis of dependence change distribution of network neighborhood at the first and second orders of network topology and the agent location is observed